Proceedings of the Ninth Annual International Conference on International Computing Education Research 2012
DOI: 10.1145/2361276.2361295
|View full text |Cite
|
Sign up to set email alerts
|

Using peer review to teach software testing

Abstract: This paper explains how peer review can be used to teach software testing, an important skill that is typically not carefully taught in most programming courses. The goals of such peer review are (1) to frame testing as a fun and competitive activity, (2) to allow students to learn from each other, (3) to demonstrate the importance of testing by uncovering latent bugs in the students' code, and (4) to provide a mechanism for evaluating testing skills. This paper explains how we added peer review to an honors d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 14 publications
0
28
0
2
Order By: Relevance
“…Smith et al [6] used peer reviews as part of a testing course. Their students, like ours, submitted double-blind reviews and wrote a report on what they learned from the review process and from evaluating the received peer reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al [6] used peer reviews as part of a testing course. Their students, like ours, submitted double-blind reviews and wrote a report on what they learned from the review process and from evaluating the received peer reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their results, 85 percent of their students considered this approach to be positive, with student feedback also indicating improved motivation and learning results. Finally, a study by Smith et al [17] discusses similar requirements for goals of developing testing course: testing activities in a university course have to be fun and competitive activity, allow students to learn from each other, demonstrate the importance of doing testing work, and provide a mechanism to evaluate the demonstrated testing skills.…”
Section: Related Researchmentioning
confidence: 99%
“…For example, earlier studies into the design and revisions of computer science course modules (for example withheld for review) have indicated that the course infrastructure and seamless integration of all different components of the course is really important to maintain the student motivation. By applying all these observations, our testing course was defined based on the recommendations by the literature reviews as follows: the course will apply access to network and social media [5], apply practical project assignments [9], promote student project works [3], teach both management and testing work in practice [6], use open source or freely available tools [11], promote some form of team work [17] and address the motivational aspects [13].…”
Section: Related Researchmentioning
confidence: 99%
“…Smith, et al [9] use peer testing in a freshman honors data-structures course. After submitting a pair-programmed assignment, each pair tests code submitted by four other pairs.…”
Section: Related Workmentioning
confidence: 99%